The Influence Of Local Food-Based Nutritional Literacy On Increasing Parents' Knowledge In Supporting The Cognitive Growth Of Primary School Age Children In Samudera District - Fauziah, Fauziah; Husna, Husna; Maulida, Maulida; Fajri, Fajri; Ayu Anora (Sean Institute, 2024)
Cognitive problems, which include disturbances in the processes of thinking, learning, and memory, can be a serious obstacle to a child's development. This condition can affect various aspects of a child's life, including academic achievement. Cognitive problems cause difficulties in learning and understanding information and can hinder academic achievement and make it difficult for individuals to participate in formal education. Indirectly, this is caused by a lack of nutritional knowledge. Efforts to increase knowledge can be carried out by implementing a local food-based nutrition literacy program which is carried out by providing interventional counseling, accompanied by recommendations for local food menus and discussions on local food menus so that it can increase nutritional knowledge of parents and mothers. The aim of this research is to determine the effect of local food-based nutritional literacy on increasing parental knowledge in supporting children's cognitive growth. This type of research is a pre-experiment design, one group pre test-post test. The population was 30 toddlers aged 7-12 months who experienced stunting during the October period in Puuk village, Samudra subdistrict, and a sample of 30 people. The sampling technique used total random sampling. Knowledge data was obtained using a questionnaire. The results of this research showed that from 30 samples the average knowledge score about nutrition was 6.2 and after providing nutritional literacy the score was 11.2. The conclusion of this research is that local food-based nutritional literacy can improve maternal nutritional cognition (knowledge).